Multiplicity and Rapidity Dependent Study of (Multi)-strange Hadrons in d+Au collisions using the STAR detector - Aggarwal Ishu (EPJ Web of Conferences)
Strangeness enhancement has long been considered as a signature of the quark-gluon plasma formation in heavy-ion collisions. Strangeness enhancement has also been observed in small systems at the Large Hadron Collider (LHC), but the underlying physics still needs to be fully understood. This motivates us to study the strange hadron production in small systems at RHIC. We present new measurements of (multi-)strange hadrons (KS0, Λ, Ξ and Ω), Λ, Ξ and Ω) in d+Au collisions at √sNN = 200 GeV, collected by STAR in 2016. We report the multiplicity and rapidity dependence of strange hadron transverse momentum (pT) spectra, pT-integrated yields dN/dy, average transverse momentum (<pT>), yield ratios of these strange hadrons to pions, nuclear modification factors and rapidity asymmetry for these particles in d +Au collisions.